Variations in 24-Hour Heart Rate, Physical Activity, Sleep, Autonomic Nervous Activity, and Motor Performance Measured Using a Multifunctional Wireless Holter Recorde in Early Childhood - KOZAKI, Ryosuke; ABE, Keiko; MIMURA, Kan-ichi; KOYAMA, Kenzo; KAGA, Masaru (European Journal of Applied Sciences, 2022)
The study aimed to implement motor performance measurements to clarify the physiological characteristics of aging, as well as the relationship between aging and motor performance. This study, we used a multifunctional wireless holter recorder to continuously measure the 24-hour heart rate, physical activity, sleep, and autonomic nervous system activity of early childhood aged 3–6 years. Results showed that average heart rate, average awake heart rate, average heart rate during sleep, and number of turns during sleep decreased with age. Basal metabolism and total energy expenditure varied significantly by age and sex. Motor performance increased significantly with age, and correlations were found between physical characteristics, physical activity, and mean heart rate during sleep. However, autonomic nervous system activity did not differ significantly with age and sex. Our results show the need for specific programs for each age group.